PEMBELAJARAN GAME EDUKASI DENGAN OBJECT-ORIENTED PROGRAMMING PADA JENJANG SMP YPK MALANG - Widodo, Romy Budhi; Swastika, Windra; Yuswanto, Yuswanto (Perkumpulan Legowo Cerdas Sejahtera, 2023)
Extracurricular activities which are supplements and complements of the curriculum have been planned in the educational calendar of a school. Although these activities are outside the curriculum, whether they are compulsory or optional activities, they play an important role in personality development and discovering student talents. Learning educational games at SMP YPK Malang is carried out in community service for the 2019/2020 period. The material uses object-oriented programming with the Greenfoot platform. The results of this extracurricular learning are evaluated with a qualitative assessment of the domain of acting skills. The assessment techniques used include practices, products, and projects. The results of the evaluation show that the aspects of student diligence and the selection of suitable materials are the dominant factors in the success of students in producing game products.